Prehispanic Settlement and Mobility in the Sama Valley, Tacna - Sarah I. Baitzel; Arturo F. Rivera Infante (Bulletin de l'Institut Français d'Études Andines)
Nestled between archaeological hotspots in southern Peru and northern Chile, the Sama Valley has only recently become the focus of intensive archaeological research, providing valuable context for the regional culture history and elucidating diachronic processes dating from the Archaic to the colonial period. This article synthesizes current research by the Proyecto de Investigación Arqueológica Valle de Sama in relation to earlier research conducted in the valley, highlighting the importance of complementary analytical scales and methodologies. The archaeology of the Sama Valley reveals complex local dynamics of continuity and change related to human mobility and resource use, including episodes of colonization driven by state expansion and political collapse shaped by the valley’s ecology and landscapes.